Negosiasi Konflik Berlatar Belakang Fanatisme Suporter Bola (Studi Kasus pada Kelompok Suporter Panser Biru dan Snex) - Yekholia Maoureenth Priharjanto; Agus Naryoso; Adi Nugroho (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Football is one of the most popular sports in Indonesia. The action of choreography and loyalty shown by their supporters' show of how fanatical the fans of Indonesian football clubs are. However, the supporters emotions that come out, sometimes cannot be controlled and are detrimental, such as causing physical injured and causing casualties. The case of dispute between the groups of supporters encourages rivalry which is still unsolved until now. One of them is in the Panser Biru and Snex groups. Although both of them support the PSIS team, the two parties often get into physical touch. Therefore, this study itself describes how the two groups of supporters who support the PSIS Semarang banner can make peace. In this research, the theories used include Conflict Theory, Dominant and Sub-cultures Group Concept, Etnocentric Concept, Face Negotiation Theory, Interaction Process Analysis, Sosioculture Theory, Conflict Resolution Theory, and Id, Ego and Superego Concept. The subjects of this study were the Panser Biru and Snex supporters groups. This research used qualitative methods with data collection using in-depth interviews. The data are then grouped, analyzed using a phenomenological approach and triangulated as a form of data verification. The results showed that the conflict arose because the two groups wanted to mutually superior and didn't want to lose because of their love for PSIS Semarang. The existing feud made them forget about the same goal, to support PSIS Semarang. The conciliatory initiative was chosen to accommodate the pretentions of supporters among groups. This negotiation is an effort to reconcile the relationship between the two groups of supporters. Negotiators came from the management of PSIS, the result of the memorandum of understanding between the two supporters' camps restored good relations between supporters for the advancement of PSIS Semarang. The role of the negotiator as an analyzer of the causes of conflict, understanding the needs of both parties and decision makers is an important key to the success of this negotiation. This peace cannot be separated from the role of persuasive communication used by the management of PSIS Semarang. The maturity of supporters is important to suppress his ego and prioritize the interests of the club to bring togetherness and increase trust which has an impact on the achievements of this Mahesa Jenar club.